Carbon xerogel as gas diffusion layer in PEM fuel cells. (13th April 2017) - Trefilov, Alexandra M.I.; Tiliakos, Athanasios; Serban, Elena C.; Ceaus, Cătălin; Iordache, Stefan M.; Voinea, Sanda; Balan, Adriana
Abstract: We investigate a novel gas diffusion layer/catalyst/membrane assembly based on low-cost carbon xerogels replacing the expensive plasma-pyrolyzed carbon black microporous layer (MPL). The tri-layer structure (carbon paper/carbon xerogel/carbon black) of the gas diffusion layer (GDL) was tailored to enhance the bi-phase (gas–liquid) flow dynamics. GDL synthesis was performed by immersing carbon paper in a resorcinol-formaldehyde-graphene oxide precursor solution, followed by thermal treatment. The end product is a carbon xerogel structure with incorporated graphene layers that counter the additional overpotential losses due to conductivity and mass-transfer limitations. MPL structure and porosity were controlled by performing xerogel crosslinking in a centrifugal field at different G-Forces, resulting in a highly conductive material with structural properties tailored to the application of interest. Highlights: Xerogels were synthesized according to the resorcinol-formaldehyde method. The starting sol gel mix was augmented with graphene oxide as the acidic catalyst. Thermal treatment in a centrifugal field induced a gradual porosity profile. Carbon paper, xerogel, and carbon black comprised the tri-layer GDL. PEM FC MEAs bearing the composite GDLs presented reasonable performances.